THE MISUNDERSTANDING OF OUTCOME MONITORING: A SYSTEMATIC LITERATURE REVIEW ON INSTRUMENTAL LEADERSHIP - Pizzolitto, Elia (European Scientific Journal, ESJ, 2022)
In this paper, through a systematic literature review, I argue that the scientific study of instrumental leadership has been the object of a misunderstanding of its fourth dimension, that is, outcome monitoring. The general conceptualization of this dimension, which interprets outcome monitoring as an activity consisting of performance supervision and feedback provision, is highly reductive. Outcome monitoring allows instrumental leaders to modify their style and behavior depending on followers’ performance and environmental conditions. After the descriptive analysis, the article presents a content analysis performed using a grounded approach. The study conducts the design of a thematic map that highlights the complex nature of instrumental leadership’s outcome monitoring, linking performance and context in a self-empowering circuit, in which instrumental leaders, through outcome monitoring, modify the contextual conditions and their actions, strategies, and behavior. Finally, I present some recommendations for further research.